2015
DOI: 10.1089/end.2013.0665
|View full text |Cite
|
Sign up to set email alerts
|

Primary Obstructive Megaureter in Infants: Our Experience with Endoscopic Balloon Dilation and Cutting Balloon Ureterotomy

Abstract: The management of primary obstructive megaureter (POM) is usually conservative, at least in the first year of life. Nevertheless, in high-grade POMs with increasing dilation, obstructive patterns found at renography, or cases involving decreased renal function, there is a clear indication for surgery. From January 2009 to March 2013, 12 patients, aged 6 to 12 months (mean 8 months), were treated endoscopically for POM. At the procedure, a clear stenotic ring was identified in 10 of the 12 patients, and a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…Recent techniques that utilize ultrasound guidance instead of fluoroscopy during PCNL and URS have been reported in children and show that the techniques can safely and effectively be performed without ionizing radiation. 6163 Future larger, prospective randomized trials are needed to validate the results of these smaller studies.…”
Section: Acute Managementmentioning
confidence: 99%
“…Recent techniques that utilize ultrasound guidance instead of fluoroscopy during PCNL and URS have been reported in children and show that the techniques can safely and effectively be performed without ionizing radiation. 6163 Future larger, prospective randomized trials are needed to validate the results of these smaller studies.…”
Section: Acute Managementmentioning
confidence: 99%
“…Endoscopic balloon dilation (EBD) of the vesicoureteral junction (VUJ) was first described by Angulo et al in 1998 as initial approach of complicated POM ( 3 ). Since then several publications have shown that EBD using the original technique or a variation of the same principle is feasible, safe, and a real less-invasive procedure even for very young patients ( 4 8 ). During last years the interest has been focused on the long term effectiveness of this procedure, based on the good long-term results and suggesting that EBD could be a valid option as the definitive treatment of POM ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that safety profiles of URS are well known, there are still some complications related to the instrument itself, such as poor visibility or poor deflection, which bears no harm to the patient and can be solved by simple instrument replacement. However, complications like locked deflection of a flexible ureteroscope while in the renal pelvis 1 or retainment of the flexible ureteroscope from accordioning of the outer scope shaft skin 2 still represent significant risks. To decrease operative time and therefore reduce costs, minimize morbidity rates, and decrease the risk of damage caused by the ureteroscope, 3 URS can be complemented by UAS.…”
Section: Discussionmentioning
confidence: 99%